Stabilization of Uncertain Switched Systems with Frequent Asynchronism via Event-Triggered Dynamic Output-Feedback Control - Jin-E Zhang; Xiangru Xing (Discrete Dynamics in Nature and Society)
This article investigates stabilization for a group of uncertain switched systems with frequent asynchronism. Without the limitation of minimum residence time, the average dwell-time strategy makes it possible for switched systems with uncertain parameters to switch frequently over successive event intervals. Since it is highbrow and expensive to obtain the whole state information in practice, the dynamic output-feedback controller is applied. With the aid of a controller-pattern-related Lyapunov functional and an event-triggered dynamic output-feedback controller, sufficient conditions are established to ensure the stability of the resulting uncertain closed-loop system. To appropriately deal with the uncertain parameters, some inequalities of the linear matrix are tactfully utilized together with the Lyapunov functional and controller gains are constructed by the strategy of the block matrix. Furthermore, the presence of the lower boundary on adjacent event intervals is earnestly discussed to eliminate the Zeno behavior. Eventually, the feasibility and availability of the theoretical results are illuminated by a numerical simulation.